2020
DOI: 10.3390/pharmaceutics12111072
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembling Tacrolimus Nanomicelles for Retinal Drug Delivery

Abstract: Neovascular age-related macular degeneration (AMD) is characterized by an increase in reactive oxygen species (ROS) and pro-inflammatory cytokines in the retinal pigment epithelium cells. The primary purpose of this study was the development of a clear, tacrolimus nanomicellar formulation (TAC-NMF) for AMD. The optimized formulation had a mean diameter of 15.41 nm, a zeta potential of 0.5 mV, and an entrapment efficiency of 97.13%. In-vitro cytotoxicity studies revealed the dose-dependent cytotoxicity of TAC-N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Such nanomicelles can be utilized to entrap hydrophobic drugs in their core. Thus, they can serve as excellent drug delivery vehicles for hydrophobic drugs and support in improving their solubility [ 9 , 10 , 11 ]. Here, we prepared HA − PTX + RTV − NMF using a mixture of polymers like HA−ss−PLGA and Vit E-TPGS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such nanomicelles can be utilized to entrap hydrophobic drugs in their core. Thus, they can serve as excellent drug delivery vehicles for hydrophobic drugs and support in improving their solubility [ 9 , 10 , 11 ]. Here, we prepared HA − PTX + RTV − NMF using a mixture of polymers like HA−ss−PLGA and Vit E-TPGS.…”
Section: Resultsmentioning
confidence: 99%
“…In summary, the combination therapy of anticancer drugs with RTV can overcome drug resistance by deactivating the overexpression of efflux transporters and metabolizing enzymes. In another study, we demonstrated the inhibition of the hypoxia-induced overexpression of HIF-α and, consequently, overproduction of VEGF and endothelial proliferation by [ 10 ]. Therefore, we anticipate that anti-cancer drug regimens containing RTV would enhance the therapeutic exposure of cancer cells to anticancer agents, potentially improving chemotherapeutic efficacy, devoid of drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…micelles made of PEG-hydrogenated castor oil-40 and octyxonyl-40, which have low CMC and provide slow drug release. Tacrolimus-loaded micelles showed faster cell internalization than the free drug [129]. Mixed micelles of polyoxyl 40 stearate and polysorbate 80 successfully delivered dexamethasone (0.1%) to the back of the eye, providing therapeutic drug levels in retina and choroid after eye drop instillation [130].…”
Section: Dexamethasonementioning
confidence: 99%
“…In recent years, nanomicelles, due to their small particle size, excellent stability, high drug loading, sustained release, have been applied in various biological and medical fields, such as Cancer-targeted therapy [16][17][18][19] , and ophthalmologic disease [20]. Nanomicelles are nano-sized colloidal carriers characterized by core-shell structures consisting of the exterior hydrophilic polar head and interior hydrophobic tail.…”
Section: Introductionmentioning
confidence: 99%